Analisis Kritis Kepemimpinan Pendidikan Islam Berdasarkan Syarat Dan Ciri-Ciri Kepemimpinan Yang Ideal - Siti Qurrotul A’yuni; Radia Hijrawan (STAI Terpadu Yogyakarta, 2020)
Islamic education institutions are places that accommodate all Islamic educational activities. In it consists of individuals to form a group. Talking about groups, of course there is someone who stands out the most and can influence others, based on that fact the term leader appears, where the process of influencing and organizing activities in the group is called leadership. The process of leadership in an educational institution has an important role for the sustainability and success of an institution. The library research method is the method used by the author in analyzing Islamic education leadership. Compiled from several literature studies in the form of print and digital, then an analysis is carried out related to ideal leadership based on its terms and characteristics, the results obtained are inevitable where there is no single leader with perfection. There is no patent formula or theory that is used by the leadership to lead the institution. However, ideal in the sense here, can be interpreted as leadership in accordance with the circumstances and conditions of the institution he leads.